THE FACES OF TIKTOK ENGLISH LEARNING INFLUENCERS OF EFL STUDENTS IN LEARNING - Maulida Amanda Putri; Hertiki (LPPM Universitas PGRI Adi Buana, 2024)
ABSTRACT English is a globally spoken language crucially taught at all educational levels in Indonesia. Despite its significance, many students struggle due to inadequate proficiency and practice, potentially dampening their motivation. Social media platforms like TikTok offer a promising avenue for language acquisition, hosting diverse educational content, including English learning videos. This study identifies TikTok English influencers as educational tools for students, exploring how these influencers enhance English proficiency among EFL students at Universitas PGRI Adi Buana Surabaya. Using qualitative descriptive research, the study delved into EFL students' perspectives through interviews, documentation, and observations. The findings indicated a positive view among students regarding TikTok influencer accounts as effective learning media. Consequently, the study concludes that leveraging TikTok influencer accounts can significantly improve students' English language skills, underscoring TikTok's potential as a valuable educational resource in language learning contexts. Kata kunci: English learning influencers, TikTok, EFL students.